MANEJO DA TIRIRICA EM CULTIVOS SUCESSIVOS DE MILHO E FEIJÃO - Brighenti, Alexandre M.; Silveira, José Sebastião M.; Sedyiama, Carlos S. (REVISTA DE AGRICULTURA, 2015)
MANEJO DA TIRIRICA EM CULTIVOS SUCESSIVOS DE MILHO E FEIJÃO